Fixed-order and merged parton-shower predictions for WW and WWj production at the LHC including NLO QCD and EW corrections - Bräuer, Stephan; Denner, Ansgar; Pellen, Mathieu; Schönherr, Marek; Schumann, Steffen (Journal of High Energy Physics, 2020)
First, we present a combined analysis of pp →μ+vμe−v¯¯¯e and pp →μ+vμe−v¯¯¯ej at next-to-leading order, including both QCD and electroweak corrections. Second, we provide all-order predictions for pp →μ+vμe−v¯¯¯e+jets using merged parton-shower simulations that also include approximate EW effects. A fully inclusive sample for WW production is compared to the fixed-order computations for exclusive zero- and one-jet selections. The various higher-order effects are studied in detail at the level of cross sections and differential distributions for realistic experimental set-ups. Our study confirms that merged predictions are significantly more stable than the fixed-order ones in particular regarding ratios between the two processes.
EPrint Processing Status: Full text deposited in DRO